Analisis Peran Budaya Organisasi Dalam Menciptakan Lingkungan Kerja Yang Berkelanjutan Pada PT. Alkan Chemical Indonesia - Sheva Prasetyo Budi Rahayu; Sungkono (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
The objective of this study is to analyze the role of organizational culture in creating a sustainable work environment at PT. Alkan Chemical Indonesia. This study is significant because companies operating in the chemical industry face challenges in achieving a safe and productive work environment. The qualitative approach with descriptive analysis was employed in this study. Data were collected through observation, interviews, and document review. The findings indicate that organizational culture plays a significant role in creating a sustainable work environment. The dimensions of core values, leadership, collaboration, and favorable working conditions were identified as crucial elements in fostering sustainability. The implementation of a robust organizational culture can enhance employee awareness and engagement in sustainability initiatives, optimize resource utilization, and ensure effective waste management. This study offers recommendations for the management of PT. Alkan Chemical Indonesia is encouraged to reinforce its organizational culture in order to facilitate the implementation of sustainable practices. This entails enhancing communication regarding the company's sustainability vision and mission, fostering collaboration across departments, and monitoring occupational health and safety. By doing so, the company can more effectively achieve its environmental sustainability objectives.